2009
DOI: 10.1177/0898264308329017
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Personhood and Achieving Quality of Life for Older Adults With Dementia in the U.S. Health Care System

Abstract: The implications of current and future public policy, avenues for further research, and strategies by which the health care community may better serve persons with dementia are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…There is a need for a broader perspective if we are to understand variations in QoL among PwD (O'Connor et al ., ). It has been suggested that domains potentially relevant to QoL in dementia include social, environmental, economic, cultural and psychological factors (Parse, ; Katsuno, ; Smith et al ., ; Byrne‐Davis et al ., ; Murray and Boyd, ; Venturato, ; Moyle et al ., ). The present findings raise questions about the association between taking AChEI medication and QoL and highlight for the first time the central importance of the perceived quality of relationship with a carer as a predictor of subsequent self‐ratings of QoL by PwD.…”
Section: Discussionmentioning
confidence: 97%
“…There is a need for a broader perspective if we are to understand variations in QoL among PwD (O'Connor et al ., ). It has been suggested that domains potentially relevant to QoL in dementia include social, environmental, economic, cultural and psychological factors (Parse, ; Katsuno, ; Smith et al ., ; Byrne‐Davis et al ., ; Murray and Boyd, ; Venturato, ; Moyle et al ., ). The present findings raise questions about the association between taking AChEI medication and QoL and highlight for the first time the central importance of the perceived quality of relationship with a carer as a predictor of subsequent self‐ratings of QoL by PwD.…”
Section: Discussionmentioning
confidence: 97%
“…A person’s ability to complete ADL is not only necessary for physical well-being, but is central to one’s independence, pride, and dignity [5,6]. An inability to complete ADL often results in a dependence on caregivers, thus increasing caregiver burden and care costs [7-9]. The associated social and economic costs (both direct and indirect) for caring for older adults, particularly those with dementia, is expected to be enormous.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that by 2050 approximately 1.5 billion people or 16% of the world's population will be aged 65 or older (World Health Organisation [WHO], 2011). Alzheimer's disease (AD) is the most common form of dementia and is most typically diagnosed in people over 65 years of age (Murray & Boyd, 2009). By 2050 it is estimated that AD will affect 1 in 85 people globally (Brookmeyer, Johnson, Ziegler-Graham, & Arrighi, 2007).…”
Section: Introductionmentioning
confidence: 99%